The role of Nigerian scholars in improving the Arabic language in the future in Nigeria - Yunusa, Dalhatu Zakariyya; Abdullahi, Yakubu (Journal of Arabic Language Studies and Teaching, 2023)
This research seeks to investigate the efforts of Nigerian Arabic scholars in developing and attracting people to learn Arabic. The aim is for local people to understand religion properly and correctly through Arabic. This research uses a qualitative descriptive research method. The data source was obtained from field observations, strengthened by data from books, journals, and literature related to the research object. This research found that Nigerian Arabic scientists use seven fields to introduce and attract people to learn Arabic: teaching and learning, national harmony, national development, state security, foreign policy, economics, media, and communication. From all these fields, it is proven that people are very enthusiastic about studying Arabic, and the Arabic language in Nigeria will develop better in the future.